DARI MAKASSAR KE MAKASSAR: ASPEK DEMOGRAFI DAN POLITIK PROSES “ETNISASI” SEBUAH KOTA - Dias Pradadimara (Populasi, 2003)
The city of Makassar, once named Ujung Pandang, in South Sulawesi, underwent tremendous transformation in the 20th century. This transformation significantly changed the image of the city from a cosmopolitan town to a provincial and “ethnic” city. This article shows that the changes of the city’s image did not happen by itself. There were changing structural conditions, namely demographic and political conditions, which allowed the changes to happen.Since early 20th century the population of the city has grown exponentially. First, in-migrants from the surrounding regions in the eastern part of Indonesia flocked into the city until early 1950s. Second, due to the rebellion and unrest in the countryside of South Sulawesi since 1950 inmigrants, mostly refugees, from Bugis-speaking areas in even larger number swarmed Makassar. Parallel with the demographical changes, the political scene in the city (and the province) was increasingly dominated by politicians and bureaucrats of South-Sulawesi origins. The Permesta rebellion in late-1950s triggered the departure of mostly non-South Sulawesi politicians away from the region leaving the political stage fully in the hands of local politicians. The “ethnic-ization” of the city was made possible by these demographical and political changes.